Measuring the Loss of Privacy from Statistics - Tschantz, Michael C.; Nori, Aditya (Workshop on Quantitative Analysis of Software, 2009)
We present a specialization of quantitative information flow to programs that compute statistics. We provide an approach for estimating the information flows present in such programs based on Monte Carlo simulation and argue that it is more accurate than previous approaches in this domain.